AKUNTABILITAS DAN TRANSPARANS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) PADA SMP NEGERI 4 RIMBA MELINTANG KABUPATEN ROKAN HILIR: (Accountability and Transparancy of Handling Operational Expense (BOS) at SMP Negeri 4 Rimba Melintang Kabupaten Rokan Hilir) - Maya Kusuma Nasution (Perspektif Pendidikan dan Keguruan, 2017)
Accountability in financial management is indispensable for is very important, the success of an organization including in educational institutions can be measured how the institutions manage financial and human resources. Management of BOS funds are needed to determine the extent of the accountability and transparency of BOS funds in Public Junior High School 2 Rimba Melintang, Rokan Hilir. This research is a qualitative case study approach. The study population is the principal, treasurer, school committees, teachers, parents and students. methods of sampling conducted the lottery. Data were analyzed with descriptive analysis. Accountability management of school operational funds (BOS) has been done by reviewing the financial management process of the threebudgeting, financial reporting, and verification reports. BOS funds management at the Public Junior High School 4 Rimba Rokan Hilir already accountable and transparent..